Triterpenoids from the stems and leaves of Schisandra incarnata. (September 2020) - Zhou, Ming; Peng, Xiaogang; Zhou, Jia; Liu, Ye; Meng, Xianggao; Ruan, Hanli
Abstract: Six undescribed triterpenoids, schincarins A‒F, categorized as the preschisanartane (schincarin A), 3, 4-secocycloartane (schincarins B‒D), 3, 4; 9, 10-disecocycloartane (schincarin E), and 3, 4-secolanostane (schincarin F) classes, along with twelve known analogues, were obtained from the stems and leaves of Schisandra incarnata Stapf. Their structures were elucidated on the basis of extensive spectroscopic analyses. The absolute configuration of schincarin A was corroborated by analysis of the experimental ECD spectrum, and single-crystal X-ray diffraction with Mo K α irradiation. Schincarin A represented the first example of preschisanartane-type triterpenoid with two oxa-bridged hemiketals. Among the selected compounds which were evaluated for immunosuppressive activities, schincarin C and kadsudilactone A showed potential inhibition against ConA-induced T-cell proliferation with IC50 values of 5.83 and 6.32  μ M, and LPS-induced B cell proliferation with IC50 values of 10.21 and 11.49  μ M, respectively. Graphical abstract: Image 1 Highlights: Six undescribed and twelve known triterpenoids were identified from Schisandra incarnata. Schincarin A represented the first example of preschisanartane-type triterpenoid with two oxa-bridged hemiketals. Schincarin C and kadsudilactone A showed potential immunosuppressive effects.